2020
DOI: 10.1002/cmdc.202000385
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Ketoamide‐Based Stereoselective Calpain‐1 Inhibitors as Neuroprotective Agents

Abstract: Calpain inhibitors have been proposed as drug candidates for neurodegenerative disorders, with ABT-957 entering clinical trials for Alzheimer's disease and mild cognitive impairment. The structure of ABT-957 was very recently disclosed, and trials were terminated owing to inadequate CNS concentrations to obtain a pharmacodynamic effect. The multistep synthesis of an α-ketoamide peptidomimetic inhibitor series potentially including ABT-957 was optimized to yield diastereomerically pure compounds that are potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…We pursued a series of ketoamides based upon published patents and computational docking studies . Of this series of compounds, 1 – 5 were observed to be potent and highly selective toward calpain-1 at 1 μM with minimal inhibitory activity against cathepsin-B, papain, and cathepsin-K (Figure B,C; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We pursued a series of ketoamides based upon published patents and computational docking studies . Of this series of compounds, 1 – 5 were observed to be potent and highly selective toward calpain-1 at 1 μM with minimal inhibitory activity against cathepsin-B, papain, and cathepsin-K (Figure B,C; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…53 AbbVie have used amnesia induced by the muscarininc Ach-receptor blocker scopolamine in preclinical development of calpain inhibitors; we have shown 5 and a nonselective calpain inhibitor to be effective in this assay. 30 However, neither REM sleep nor scopolamine-induced amnesia provide a test of the calpain−cathepsin hypothesis.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Binding of 119 (A) and 140 (B) in the active site of calpain-1. 206 Reproduced with permission from ref ( 206 ). Copyright 2020 Wiley-VCH GmbH.…”
Section: α-Ketoamide As a Reactive Moiety In Potential Drugsmentioning
confidence: 99%
“…Growing studies have shown that calpain is involved in many diseases, including cardiovascular diseases, cancer, neurodegenerative diseases and several other diseases. [20][21][22][23][24] Consistent with previous studies, 9 our results showed that hypoxia elevated calpain-1 protein levels in both lung tissues of mice with HPH and PASMCs, significantly increased RVSP, right ventricular hypertrophy and vessel wall thickness, increased the expression of PCNA, Ki-67, α-SMA and the formation of collagen fibre in the lung tissues, and enhanced the It has been reported that calpain-1 is involved in the formation of fibrosis by regulating the expression of angiopoietin-1, IL-6, MMP2, collagen I and III. Besides, calpain-1 overexpression can also induce activation of TGF-β1/Smad signalling pathway in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%